Forecast of the development of sectors of the national economy in Slovakia - Peter Burger; Viera Hovančíková (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
This paper aims to estimate the expected development of the share of employees in sectors of the national economy in selected regions of Slovakia (Bratislava, Košice, and Prešov Regions) and in the Slovak Republic as a whole up to 2025. It also predicts which sectors of the national economy (primary, secondary, tertiary or quaternary) will grow in Slovakia in 2020-2025 and which sectors will stagnate or decline. The results predict a steadily declining share of people employed in the primary and secondary sectors in Slovakia and in the self-governing regions investigated. In contrast, the share of the quaternary sector in total employment is likely to increase up to 2025 both in Slovakia and in the Bratislava and Košice Regions. The share of employees in the tertiary sector is expected to grow in Slovakia, but at the same time it is confirmed that in the Bratislava Region there is a gradual reallocation of employees working in the services sector and an increase in the share of employees working in the quaternary sector at the expense of the tertiary sector. This expected development of the shares of employees in the individual sectors and, in particular, the increase in the share of employees in the quaternary sector are in line with the reallocation of the shares of employees in the sectors of the national economies of the developed EU countries, especially the countries of Western and Northern Europe.
Keywords: J21; O11; O14; 330; Sectoral Division; Sectoral Change; Share of Employees; Quaternary Economy; Employment Trends; National Economy